Immediate postoperative lumbar spine magnetic resonance imaging: Correlation with postoperative pain in lumbar microdiscectomy. Issue 43 (28th October 2022) - Noh, Sung Hyun; Ndraha, Eveline; Shin, Dong Ah; Cho, Pyung Goo; Kim, Keung Nyun; Kim, Sang Hyun
Abstract : Magnetic resonance imaging (MRI) has been extensively used in the management of patients with a herniated lumbar disc. Nevertheless, immediate postoperative MRI has not become a standard procedure, with limited research suggesting that the findings are often similar to preoperative MRI in both symptomatic and asymptomatic patients. This study aimed to determine the benefits of immediate postoperative MRI in patients with or without postoperative symptoms and its correlation with these symptoms. A total of 172 patients who underwent lumbar spine microdiscectomy at our institution between 2014 and 2021 were included. Patients who had previous spinal surgery and lumbar fusion were excluded. Patient data were collected from medical records. MRI was performed 3 days after surgery and assessed by 2 neurosurgeons to minimize bias. Immediate postoperative MRI results showed dural sac compression or foraminal stenosis in 29 patients (16.86%), of which 10 had postoperative pain and 19 were pain free. Among the 143 patients (83.14%) without these findings on MR imaging, 38 had postoperative pain. Immediate postoperative MRI did not correlate with postoperative pain ( P = .421/.357). Intraoperative bleeding and the Charlson comorbidity index (CCI) showed significant correlations with postoperative pain ( P = .018 and .002, respectively). In a multivariate analysis, intraoperative blood loss and CCI independently correlated with postoperative pain ( P = .001 and .001, respectively). Based on our findings, intraoperative blood loss and CCI appear to be the factors that may predict the persistence of postoperative pain, despite normal findings on MRI.